A partiumi autonómia történelmi és társadalomföldrajzi alapjai - Süli-Zakar, István; Szilágyi, Ferenc (Közép-Európai Közlemények, 2014)
The peculiarity of the Partium region lies in its role of connecting the Transylvanian and the Pannonian basins. There can be distinguished several stages in its history. Its formation stems from the geopolitical situation after the partition of Hungary in 1526. Transylvania becomes politically autonomous and holds control over comitats in eastern Hungary as well. The name of the region comes from the phrase PARTS (Latin Partium) of eastern Hungary. Its separate status within the Hungarian Crown was maintained until the Compromise. After the Treaty of Trianon in 1920, many new region names came into being in the Carpathian Basin. In the areas annexed to Romania the historical Transylvania and the Banat region can be clearly identified, but next to them there is the eastern part of the Tiszántúl region, too. The former name Partium will be used again to denominate this area. Today, this region with a mixed Hungarian and Romanian population is struggling to survive. At present, there is no such region in Romania either from an administrative or a statisticalpoint of view, while in the case of both ethnic groups there exists a regional identity (Partium for the Hungarians and Crigana for the Romanians). Nowadays, the demand for autonomy has also arisen on behalf of the local Hungarian community.